If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -18 = 65 Reorder the terms: -18 + X = 65 Solving -18 + X = 65 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + X = 65 + 18 Combine like terms: -18 + 18 = 0 0 + X = 65 + 18 X = 65 + 18 Combine like terms: 65 + 18 = 83 X = 83 Simplifying X = 83
| 16=n/2 | | 28=4x-2(-x+4) | | 16=n/2 | | 3.14*6*6*5= | | (-27)-12= | | (35X^2-11X-8)/(5X+2) | | 6x+7=-9 | | 3nx^8-6nx^4-45n=0 | | 7k^2-14k=-7 | | (x^2)+14x+24=0 | | -8=-4x-2(x-11) | | 3.14*5*5*12= | | (2r+8)=88 | | (2r+8)=88 | | 2x+2(x-3)=30 | | 90xX=45 | | X^2-38x+4=0 | | x^9-27=0 | | -8+(-11)= | | 5m^2-7m-2= | | -48x-34=60 | | x+90=45 | | 7x^3-28x-35x=0 | | 12^8/35t^6 | | 5x^2+11x+38=0 | | -5(-8)= | | 3.14*5*5*7= | | X^2+7x+3=4 | | A=3.14(5square)(7) | | 6-4x=-22 | | 3x-3(7x+9)=81 | | 6=1a/4+2 |